The Role of Learning Motivation and Social Interaction in Enhancing Students' Speaking Skills: Managerial Perspectives in Educational Management - Nasihin, Nasihin; Khoirun, Fattah; Aminudin, Aminudin; Mastur, Al Akcbar (Journal of Educational Management Research, 2025)
This study examines the role of learning motivation and social interaction in enhancing eighth-grade students' Arabic language acquisition, with a focus on speaking skills. The purpose of this research is to explore how intrinsic and extrinsic motivation impact students' persistence, practice enthusiasm, and confidence in using Arabic in everyday contexts. Additionally, the study investigates how social interaction within the classroom influences language learning, particularly through communication dynamics. A learning management perspective is used to assess how classroom organization, activity planning, teaching strategies, and the use of time and media affect language acquisition. Using a mixed-methods approach, data were collected through surveys, interviews, and classroom observations. The findings reveal that intrinsic motivation, such as curiosity and personal satisfaction, as well as extrinsic factors, like recognition and social support, significantly enhance Arabic language acquisition. Furthermore, social interaction through activities like role-play and group discussions fosters authentic practice and reduces anxiety. The study concludes that combining motivation, social interaction, and effective learning management leads to improved oral communication skills, promoting more natural, argumentative, and emotionally engaging speech.